Factors influencing job satisfaction among employees in Malaysian manufacturing industry during Covid-19 pandemic - Syazana Hawani, Shaari (2020)
The insurgence of COVID-19 outbreak led to various consequences particularly on the economic condition of every country such as in term of the financial crisis in tourism industry, and declining of investment and trade. These consequences will affect the way on how a company operate their business and the employees. Hence, many professionals in human resource management as well as psychology are targeting to investigate the impacts on the employees. This research intends to identify the relationship of technostress, career uncertainty and career adaptability with job satisfaction among manufacturing employees in Malaysia during the Covid-19 pandemic. In order to attain the findings, an online survey was distributed to two manufacturing companies at northern region of Malaysia. A total of 400 questionnaires were answered and utilized for data analysis. The result of multiple regression analysis results indicated that technostress, career uncertainty and career adaptability have statistically significant contribution with job satisfaction. Finally, information pertaining to the limitations, implications, recommendation and conclusion of the study were also explained in this research paper.